2021
DOI: 10.1016/j.jcjd.2020.08.104
|View full text |Cite|
|
Sign up to set email alerts
|

Conversations and Reactions Around Severe Hypoglycemia Study: Results of Hypoglycemia Experiences in Canadian Adults With Insulin-Treated Diabetes and Their Caregivers

Abstract: Despite advances in therapy and technology, persons with diabetes on insulin therapy remain at risk for severe hypoglycemia. Severe hypoglycemic events occur outside the health-care system and are not always discussed at health-care visits. Thus, events may remain unknown to providers. This study highlights the experiences and psychosocial impact of severe hypoglycemia on persons with diabetes and their caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 29 publications
3
20
1
Order By: Relevance
“…Similar to the UK and Canadian [14] cohorts, Japanese PWD often consume sugar in order to recover from an SH event when possible. However, rescue treatment of SH in Japan some notable differences in comparison to other countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the UK and Canadian [14] cohorts, Japanese PWD often consume sugar in order to recover from an SH event when possible. However, rescue treatment of SH in Japan some notable differences in comparison to other countries.…”
Section: Discussionmentioning
confidence: 99%
“…The study design has been previously described [14]. Briefly, CRASH was a cross-sectional, online survey conducted in eight countries (Canada, China, France, Germany, Japan, Spain, USA, UK).…”
Section: Study Design and Participant Enrollmentmentioning
confidence: 99%
“…A rating of ≥ 4 indicates the PWD has ‘impaired awareness of hypoglycemia’. Study methodology and country-specific findings were reported previously [2] , [3] , [4] .…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have identified the psychosocial and emotional burden of SH in family members and other caregivers of PWDs. [3][4][5][6][7][8] An integrative review of 11 studies that assessed the experience of partners of adults with type 1 diabetes identified that partners made attempts to minimize hypoglycemia in their PWD and the potential for SH and, as a result, experienced considerable distress and disrupted lives. 5 Furthermore, although partners have identified the need to remain calm in a SH emergency in order to more clearly think about how to help, many remain unprepared and anxious about their ability to administer IG in an emergency.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…3,4 Furthermore, the impact of witnessing SH episodes and potential need for them or others to provide assistance to a family member in a SH emergency presents many caregivers with a significant emotional burden and anxiety. [5][6][7][8] A major issue that hinders effective SH rescue is the unpredictability of when a SH event will occur, potentially leaving the responsibility of rescue to unprepared and untrained caregivers or bystanders. Secondly, the life-threatening nature of SH in PWDs may present a large emotional burden and increase the mental and temporal demand on caregivers, potentially affecting their performance during rescue.…”
Section: Introductionmentioning
confidence: 99%